The 'Great Matter' of King Henry VIII. (8th January 2017) - Ward, Ian
ABSTRACT: Scholars have long surmised that The Famous Life of King Henry VIII was very probably the last play that Shakespeare had a part in writing. The first recorded performance of the play was in 1613. The play was more closely about a particular 'moment' in the reign of King Henry VIII; the events that surrounded his divorce from Katherine of Aragon. Shakespeare chose this moment because he appreciated its larger significance. The consequence would be the Reformation and the establishment of the Anglican Church. Henry VIII remains a relatively neglected part of the Shakespearian canon. But there is, for scholars interested in the place of law within this canon, a particular significance in Shakespeare's final play. In all the other histories, there are lots of soldiers and lots of battles. There are none in Henry VIII . In place of war, there is law.